Knowledge and Practices on Preventive Measures of Blood Borne Diseases Among Non-Medical Attendants Working in Dhulikhel Hospital, Kathmandu University Hospital - Sanjel, S; Tuladhar, S; Khanel, K (Kathmandu University Medical Journal, 2015)
Background Blood and certain body fluids pose the greatest threat to health due to sharp injuries spreading blood borne pathogens that cause serious illness when transmitted. Despite the high sickness rate, sanitation staff lacked awareness regarding protections from contacting soiled materials while handling biomedical wastes. Objective The study aims to find out the knowledge and practices on preventive measures of blood borne diseases among non-medical attendants. Method Descriptive cross-sectional study was conducted to find out the knowledge and practices on preventive measures on blood borne diseases among all the 53 non-medical personnel in Dhulikhel Hospital, Kathmandu University Hospital. Respondents scoring ≥50% on knowledge score were taken as having adequate knowledge. A Nepali version of pre-tested structured and semi-structured questionnaire was used to conduct interview. Participation in the study was voluntary and written consent was taken before inquiry. Outcomes were measured in both descriptive and inferential ways. Result The adequate knowledge was found among 86.8% of the respondents on the blood borne diseases whereas 50.9% of them had proper practice on it. Although, there is poor positive correlation between the mean knowledge score and literacy, the correlation was significant (r = 0.341, p < 0.05). Alike, the mean practice score and work experience demonstrated significant correlation (r = 0.319, p <0.05). Conclusion Although knowledge score of male was high, female had higher practices score. Both knowledge and practice score increased due to the participation in the training programs and increment in experience. There was significant positive correlation between the mean knowledge score and literacy, and the mean practice score and work experience. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12506 Kathmandu Univ Med J 2013; 43(3):210-215